Mechanical vibrations - Den Hartog, J. P. 1901-1989 (Dover Publications, 1985)
This classic text combines the scholarly insights of its distinguished author with the practical, problem-solving orientation of an experienced industrial engineer. Topics include the kinematics of vibration, degrees of freedom, gyroscopic effects, relaxation oscillations, Rayleigh's method, and more. Abundant examples and figures, plus more than 230 problems and answers. 1956 edition.
Reprint. Originally published: 4th ed. New York : McGraw-Hill, 1956. With a new preface.
Includes index.
Keywords: Vibration.; Mechanics, Applied.; elektronické knihy; electronic books